The Structure of the Course on the Concept of Modern Natural Science with the Use of Computer Technologies - D A Denisova; N G Levanova; A P Pavlova (Peoples' Friendship University of Russia (RUDN University), 2012)
The outline of the Concept of Modern Natural Science (CMNS) course is discussed in the article. The course comprises the information on the natural-science cycle and is developed for the students of the economic, sociological and humanitarian trends of training. The structure of the course is suggested. The kinds of activities of the student and the forms of knowledge control are considered.